Influence of Social Construct on Consumers’ Brand Purchase Intention: a Review of Research - Kumar Rup, Bikash; Gochhayat, Jyotiranjan; Samanta, Sasmita (International Journal of Engineering and Technology, 2018)
The aim of this study is to reveal the impact and influence of social construct on consumers’ brand purchase intention. Within the study the latent idea is to illuminates the influence of social construct on brand personality, which leads to enhance the brand purchase intention. The flow of effect of social construct is directly to purchase intention or through brand attitude. In different cultural point of view the specific dimensions of brand personality, those are more influential on purchase intention need to be identified. The outcome of the study may helpful for marketers to redesign their marketing strategy in accordance with the consumers brand personality.